Determinant factors of stunting children aged 24-59 month - Astrid Aulia Purnamasari; Warsiti Warsiti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Stunting remains a major public health concern in Indonesia, particularly among children under five years of age. In the working area of Puskesmas Minggir, Sleman Regency, a total of 55 stunted children were identified across five villages in 2025. The determinants of stunting are multifactorial, encompassing nutrition, maternal, and socioeconomic demensions. Purpose: To identify the determinant factors associated with stunting in children aged 24-59 month. Method: A quantitative observational analytic study with a cross-sectional design was conducred from January 15-18 2026, in Sendangrejo Village. A total of 64 respondents (16 stunted, 48 non- stunted) were included. Variables examined were maternal height, maternal education, birth weight, birth length, exclusive breastfeeding, history of infectious disease, child’s sex, and family income. Data were analyzed using univariate and bivariate (Fisher’s Exact test and Chi-Square) analyses. Results: Of 64 children, 16 (25%) were classified as stunted. Bivariate analysis revealed a significant association between maternal education level and stunting (p = 0.002). Other variables-maternal height, birth weight, birth length, exclusive breastfeeding, history of infectious disease, child’s sex, and family income did not show statistically significant associations (p > 0.05) Conclusion: Maternal education level the determinant factor with a statistically significant association with stunting in children aged 24-59 months. Improving access to education for women is an important strategy in stunting prevention efforts.